A home security system for seniors based on the beacon technology. (27th April 2018) - Wu, Hsin‐Te; Tsai, Chun‐Wei
Summary: Many elderly people have a hard time adapting to information technology (IT); for instance, many wearable devices have such rich functions that render them highly power‐consuming, creating operational difficulties for the elderly. The wearable devices must constantly be recharged, which is also an issue for disabled elderly people. Hence, this study utilizes transmitter and receiver of the beacon to learn about the habits of elderly people in their residence while monitoring their heart rate to track their physical condition; when and if they press the medical alarm, help can be sent on their way. This study uses the beacon device to position the location of elderly people in their residence. We have developed a wearable wristband that transmits data through the beacon. The only button on the wristband is a medical alarm; other functions include home positioning and heart rate monitoring, which operate automatically to relieve the elderly people from information technology adaptation issues. This paper will also develop an integrative monitoring platform that aims at detecting whether an elderly person has pressed the medical alarm as well as analyzing whether their heart rate is regular. Given that elderly people stay mostly within the range of their residence, the platform will conduct statistical analysis on schedule of the elderly person of being in and out of the house; if they have left their house for too long or have displayed irregular behavior in leaving or entering the house, then their family will be notified. The proposed method has added privacy and access authority control to prevent malicious parties from tracking the schedule or the residence of elderly people from being invaded. This study has also completed application development and conducted privacy efficacy analysis.